Learning PHP Data Objects : a beginner's guide to PHP Data Objects, Database Connection Abstraction Library for PHP 5. - Popel, Dennis (From technologies to solutions., 2007)
"This book will teach you how to use the PDO, including its advanced features. Readers need to be aware of the basics of data abstraction and should be familiar with PHP. This book starts with an overview of PHP Data Objects (PDO), followed by getting started with PDO. Then it covers error handling, prepared statements, and handling rowsets, before covering advanced uses of PDO and an example of its use in an MVC application. Finally an appendix covers the new object-oriented features of PHP 5"--Resource description page